2014
DOI: 10.1371/journal.pone.0106441
|View full text |Cite
|
Sign up to set email alerts
|

RGDechi-hCit: αvβ3 Selective Pro-Apoptotic Peptide as Potential Carrier for Drug Delivery into Melanoma Metastatic Cells

Abstract: αvβ3 integrin is an important tumor marker widely expressed on the surface of cancer cells. Recently, we reported some biological features of RGDechi-hCit, an αvβ3 selective peptide antagonist. In the present work, we mainly investigated the pro-apoptotic activity of the molecule and its ability to penetrate the membrane of WM266 cells, human malignant melanoma cells expressing high levels of αvβ3 integrin. For the first time we demonstrated the pro-apoptotic effect and the ability of RGDechi-hCit to enter int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…RGDechi encompasses a cyclic portion, containing the RGD triad for integrin binding, and a linear sequence derived from the C‐terminal fragment of the echistatin protein conferring specificity for β 3 subunit, as demonstrated by mutation and photoaffinity cross linking experiments and NMR conformational analysis combined with docking studies . In vitro and in vivo studies proved the selective binding of this peptide to α v β 3 integrin and a recent structural analysis performed in presence of isolated cell membranes has detailed the key structural determinants of this interaction . Noteworthy, the structural data confirmed that the selectivity of the peptide derives from its combined nature: while the RGD motif recognizes the extracellular domain of α v β 3 (but also other integrins), the C‐terminal fragment provides specificity for α v β 3 .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…RGDechi encompasses a cyclic portion, containing the RGD triad for integrin binding, and a linear sequence derived from the C‐terminal fragment of the echistatin protein conferring specificity for β 3 subunit, as demonstrated by mutation and photoaffinity cross linking experiments and NMR conformational analysis combined with docking studies . In vitro and in vivo studies proved the selective binding of this peptide to α v β 3 integrin and a recent structural analysis performed in presence of isolated cell membranes has detailed the key structural determinants of this interaction . Noteworthy, the structural data confirmed that the selectivity of the peptide derives from its combined nature: while the RGD motif recognizes the extracellular domain of α v β 3 (but also other integrins), the C‐terminal fragment provides specificity for α v β 3 .…”
Section: Introductionmentioning
confidence: 78%
“…The effect of RGDechi (synthesized as previously reported) on the adhesion of K562 cells seeded onto fibronectin (extracellular matrix recognizing a range of different integrins, including α v β 3 and α 5 β 1 receptors) or, alternatively, on α 5 β 1 antibody was studied in the specific cell adhesion buffer as reported in a previous manuscript …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of peptides on cell adhesion on different matrices or specific antibodies was tested on 96 multiplates (NUNC MaxiSorp from Dasit Sciences, Milano, Italy) coated with vitronectin, fibronectin or collagen (10 μg mL −1 ) (Millipore, USA) or α v β 3 and α v β 5 antibodies (10 μg mL −1 ) (Millipore, USA) . About 1.5 × 10 4 cells/well were seeded and incubated for 1 hr in the presence (50 μM) of peptides or cE5 (expressed and purified as described elsewhere) .…”
Section: Methodsmentioning
confidence: 99%